What's maths all about? - Frith, Alex; Lacey, Minna Larkum, Adam (Usborne London, 2015)
Covering a wide range of maths topics, from algebra to geometry, charts and statistics, this book answers every student's favourite question: 'why do I need to learn this stuff?'